Fast neutron absorbed dose distributions in the energy range 0.5-80 meV--a Monte Carlo study - Söderberg, J; Carlsson, G A (Physics in medicine & biology, 2000)
Neutron pencil-beam absorbed dose distributions in phantoms of bone, ICRU soft tissue, muscle, adipose and the tissue substitutes water, A-150 (plastic) and PMMA (acrylic) have been calculated using the Monte Carlo code FLUKA in the energy range 0.5 to 80 MeV. For neutrons of energies < or = 20 MeV, the results were compared to those obtained using the Monte Carlo code MCNP4B. Broad-beam depth doses and lateral dose distributions were derived. Broad-beam dose distributions in various materials were compared using two kinds of scaling factor: a depth-scaling factor and a dose-scaling factor. Build-up factors due to scattered neutrons and photons were derived and the appropriate choice of phantom material for determining dose distributions in soft tissue examined. Water was found to be a good substitute for soft tissue even at neutron energies as high as 80 MeV. The relative absorbed doses due to photons ranged from 2% to 15% for neutron energies 10-80 MeV depending on phantom material and depth. For neutron energies below 10 MeV the depth dose distributions derived with MCNP4B and FLUKA differed significantly, the difference being probably due to the use of multigroup transport of low energy (< 19.6 MeV) neutrons in FLUKA. Agreement improved with increasing neutron energies up to 20 MeV. At energies > 20 MeV, MCNP4B fails to describe dose build-up at the phantom interface and penumbra at the edge of the beam because it does not transport secondary charged particles. The penumbra width, defined as the distance between the 80% and 20% iso-dose levels at 5 cm depth and for a 10 x 10 cm2 field, was between 0.9 mm and 7.2 mm for neutron energies 10-80 MeV.